2021
DOI: 10.3389/fpsyt.2021.643704
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Factors Affecting Mental Health and Well-Being of Asylum Seekers and Refugees in Germany

Abstract: Background: Since the onset of the 2015 European refugee crisis, ~4. 46 million people have sought asylum in the European Union, with Germany logging the largest share of all asylum applications. In addition to the severe adversities before and during flight, the process of settling into a new environment involves stressors that affect psychological well-being and mental health. The aim of this systematic review was to examine contextual factors during post-migration that influence the mental health and well-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 87 publications
8
68
0
1
Order By: Relevance
“…However, refugees have been shown to continue having lower employment rates than other immigrants and natives, even ten years after migration [ 33 ]. Moreover, adequacy of income and employment have been shown to be significant predictors of general mental health for resettled refugees [ 34 , 35 ] and to moderate the adverse mental health effects of pre- and peri-migratory stressors experienced by refugees [ 36 ]. Barriers to employment identified by refugees include adverse effects of PTSD, problems with professional recertification and economic barriers to pursuing education [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, refugees have been shown to continue having lower employment rates than other immigrants and natives, even ten years after migration [ 33 ]. Moreover, adequacy of income and employment have been shown to be significant predictors of general mental health for resettled refugees [ 34 , 35 ] and to moderate the adverse mental health effects of pre- and peri-migratory stressors experienced by refugees [ 36 ]. Barriers to employment identified by refugees include adverse effects of PTSD, problems with professional recertification and economic barriers to pursuing education [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, a meta-analysis has confirmed high prevalence rates in studies within Germany of refugees and asylum seekers from many different countries of origin ( 48 ). And a recent review of postmigration contextual factors has identified a range of risk factors, such unresolved asylum status, separation from family, and discrimination ( 212 ).…”
Section: Destination Countriesmentioning
confidence: 99%
“…All of these factors make refugees particularly vulnerable in regard to their health situations: previous studies have found that up to 30 percent of adult refugees suffer from health impairments ( Fazel et al, 2005 ; Robjant et al, 2009 ; Bakker et al, 2014 ; Giua, 2017 ). It is, therefore, not surprising that some scholars have termed the situation of refugees in Germany as a mental health crisis ( Schauer, 2016 ; Hajak et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The handful of studies examining the health status of recent refugees in Germany ( Dietrich et al, 2019 ; Walther et al, 2020 ; Jaschke and Kosyakova, 2021 ; Löbel and Jacobsen, 2021 ) have focused primarily on access to healthcare services and the role of family ties abroad, as well as the role of pre- and postarrival stress for psychological and physical health and psychological distress ( see meta-analysis by Hajak et al, 2021 ). These studies, however, mainly focused on the level differences while neglecting the role of the postarrival experiences for the development of health outcomes over the duration of the stay.…”
Section: Introductionmentioning
confidence: 99%